Emergency Remote Learning in a Foreign Language Learning: The Parents' Involvement - Rizka Safriyani; Ahmad Fauzi; Siti Asmiyah (Universitas Bengkulu, 2022)
The Covid-19 pandemic outbreak has raised the emergence of remote teaching and learning process, including foreign language learning such as English and Arabic. Existing studies in context emergency remote learning have mainly focused on methods, strategies, assessment, and teachers' and students' challenges. Meanwhile, parents as 'substitute' teachers seem to be missed from exploration. This two-phased mixed method study explores the roles parents play with their children's learning of English and Arabic as foreign languages in Indonesia. Quantitative data were collected by distributing online questionnaires and analyzed using SPSS25. Forty-two (42) parents with children aged 6-18 selected through snowball sampling responded to the questionnaires. Six (6) parents were interviewed to get in-depth qualitative-exploratory data on parental involvement. The responses were transcribed, coded and categorized based on the main themes related to parental involvement. The two sets of quantitative and qualitative data in corroboration were used to draw conclusion. The findings suggest roles in controlling, motivating, and managing the learning time as the parents' most salient involvements. The results also highlight some strategies the parents take when their children learn the two foreign languages. Recommendations for schools and teachers to optimize parental involvement in remote learning for foreign languages are also presented